STUDI TENTANG MASALAH PENEMPATAN FASILITAS BERKAPASITAS SATU SUMBER DUA ESELON - Sinambela, Lamtiur (Journal Information System Development (ISD), 2017)
Facility location problem is an important part of integer programming problems, with application in the field of telecommunications, and transportation industry. This study discussed the facility location problem with two echelon. Each second echelon facilities haveÂ  limited capacity and can only be supplied by a facility on second echelon. Each customer is served only by a single facility in second echelon. The number and location of the second echelon of custumers to facilities determined echelon two simltaneous. This study addresses the questions of decision-making in designing cargo distribution system where there is a two echelon distribution system the two level structure, components and issues related decisions. The purpose of the model in the study is to determine the location of facilities at each echelon which is a distribution facility and cargo capacity at the facility so that can minimize the total cost of the minimum as the optimal solution of the modeling.Â Keywords: CFLP, integer programming, optimization, two echelonÂ